Evaluation of the 5- vs. 7-day CIDR program in dairyheifers before timed artificial insemination - H.I. Jr. Mellieon; Stephanie Leeann Pulley; G.C. Lamb; J.E. Larson (Kansas Agricultural Experiment Station Research Reports, 2011)
Our objectives were to determine: (1) the effectiveness of an injection of PGF2αto regress the corpus luteum before initiating an timed artificial insemination (TAI) program, (2) ovulation response to gonadotropin-releasing hormone (GnRH), and (3) pregnancy outcomes in dairy heifers inseminated with conventional and gender-biased semen. Heifers (n = 545) from 3 locations (Florida, Kansas, and Mississippi) were assigned randomly to 1 of 2 treatments: (1) 25-mg prostaglandin F2α(PGF2α) injection and controlled internal drug release (CIDR) insert on day −7 followed by 100 Î¼g of GnRH administered on day −5, and a 25-mg PGF2α injection at CIDR insert removal (7D) on day 0; or (2) 100 Î¼g of GnRH and insertion of previously used autoclaved CIDR on day −5 and a 25-mg PGF2αinjection at CIDR removal (5D) on day 0. Artificial insemination occurred after detected estrus from days 0 to 3. Those heifers not detected in estrus were inseminated on day 3 (72 hours after PGF2α) and given a second 100-Î¼g dose of GnRH (72 hours after CIDR removal). Blood collected on days −7 and −5 was assayed to determine concentrations of progesterone and presence of a CL (progesterone ≥1 ng/mL) on d −7. Blood progesterone concentrations on days 0 and 3 were used to determine if luteolysis occurred in all heifers. Pregnancy was determined on days 32 and 60 and intervening pregnancy loss was calculated. Of those heifers in the 7D treatment having progesterone ≥1 ng/mL on day −7, the proportion having progesterone /mL 2 days later (luteolysis) was greater (P<0.05) than that in the 5D treatment (43.0 vs. 22.9%), respectively. A treatment by location interaction was detected for pregnancies per AI. The Kansas location had no detectable treatment differences. In contrast, the 7D treatment produced more (P<0.05) pregnancies in the first replicate of the Florida location and at the Mississippi location. We concluded that the 5D protocol was not more effective in producing acceptable luteolysis, pregnancy, and ovulation rates compared with the modified 7D protocol.; Dairy Day, 2011, Kansas State University, Manhattan, KS, 2011; Dairy Research, 2011 is known as Dairy Day, 2011
Keywords: Dairy Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-176-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1057; Dairy; CIDR; Progesterone; Timed artificial insemination (TAI)